Do we know enough about the immune pathogenesis of acute coronary syndromes to improve clinical practice? - Matusik, Pawel; Guzik, Bartlomiej; Weber, Christian; Guzik, Tomasz J. (Thrombosis and Haemostasis, 2012)
Morbidities related to atherosclerosis, such as acute coronary syndromes (ACS) including unstable angina and myocardial infarction, remain leading causes of mortality. Unstable plaques are inflamed and infiltrated with macrophages and T lymphocytes. Activated dendritic cells interact with T cells, yielding predominantly Th1 responses involving interferon-gamma (IFN-γ) and tumour necrosis factor-alpha (TNF-α), while the role of interleukin 17 (IL-17) is questionable. The expansion of CD28nullCD4 or CD8 T cells as well as pattern recognition receptors activation (especially Toll-like receptors; TLR2 and TLR4) is characteristic for unstable plaque. Inflammation modifies platelet and fibrin clot characteristics, which are critical for ACS. Understanding of the inflammatory mechanisms of atherothrombosis, bridging inflammation, oxidative stress and immune regulation, will allow for the detection of subjects at risk, through the use of novel biomarkers and imaging techniques including intravascular ultrasound, molecular targeting, magnetic resonance imaging (MRI) and 18F-fluorodeoxyglucose (18F-FDG) positron emission tomography (PET). Moreover, understanding the specific inflammatory pathways of plaque rupture and atherothrombosis may allow for immunomodulation of ACS. Statins and anti-platelet drugs are anti-inflammatory, but importance of immune events in ACS warrants the introduction of novel, specific treatments directed either on cytokines, TLRs or inflammasomes. While the prime time for the introduction of immunologically inspired diagnostic tests and treatments for atherosclerosis have not come yet, we are closer than ever before to finally being able to benefit from this vast body of experimental and clinical evidence. This paper provides a comprehensive review of the role of the immune system and inflammation in ACS.Note: The review process for this manuscript was fully handled by G. Y. H. Lip, Editor in Chief.
Keywords: Acute myocardial infarction; atherothrombosis; inflammation; atherosclerosis; immunity